Holocene slope dynamics in Sierra Nevada (south Spain): sedimentological analysis of solifluction landforms and lake deposits - Oliva, Marc (2019)
The activity of geomorphic processes in the current periglacial belt of Sierra Nevada during the Holocene has been strongly controlled by climate variability. We examined two sedimentary records showing several cycles with varying intensity of slope processes in the massif. Chronostratigraphic studies of solifluction landforms have revealed seven cycles of enhanced slope activity in Sierra Nevada during the last 7 ka. Lake sediments show eight periods with increased slope activity over the last 6 ka. Depending on temperature and moisture regime, erosion or conditions of slope stability prevailed. Cold and wet periods triggered slope processes and favoured deposition of coarse-grained sediments into the lakes, whereas warm phases were prone to soil development and fine-grained sedimentation in the lakes. The lake sediments also show evidence for an increasing aridity trend since the Holocene Optimum Warm Period in Sierra Nevada, which induced a shift of solifluction processes to higher elevations accompanying late-lying snow patches.